Kinetic modeling and parametric imaging of 18F‐PSMA‐11: An evaluation based on total‐body dynamic positron emission tomography scans - Yuan, Hui; Zhang, Guojin; Sun, Taotao; Ren, Jingyun; Zhang, Qing; Xiang, Zeyin; Liu, Entao; Jiang, Lei (Medical physics (Lancaster), 2024)
Background The prostate‐specific membrane antigen (PSMA) targeted positron‐emitting tomography (PET) tracers are increasingly used in clinical practice, with novel tracers constantly being developed. Recently, 18F‐PSMA‐11 has been gaining growing interest for several merits; however, direct in vivo visualization of its kinetic features in humans remains lacking. Purpose To visualize the kinetic features of 18F‐PSMA‐11 in healthy subjects and patients with prostate cancer derived from the total‐body dynamic PET scans. Methods A total of 8 healthy volunteers (7 males; 1 female) and 3 patients with prostate cancer underwent total‐body PET/CT imaging at 1 and 2 h post injection (p.i.) of 18F‐PSMA‐11, of which 7 healthy subjects and 3 patients underwent total‐body dynamic PET scans lasting 30 min. Reversible two‐tissue compartments (2TC) and Patlak models were fitted based on the voxel‐based time activity curves (TACs), with the parametric images generated subsequently. Additionally, semi‐automated segmentation of multiple organs was performed in the dynamic images to measure the SUVmean at different time points and in the parametric images to estimate the mean value of the kinetic parameters of these organs. Results 18F‐PSMA‐11 showed quick accumulation within prostate cancer, as early as 45 s after tracer injection. It was rapidly cleared from blood circulation and predominantly excreted through the urinary system. High and rapid radiotracer accumulation was observed in the liver, spleen, lacrimal glands, and salivary glands, whereas gradual accumulation was observed in the skeleton. Prostate cancer tissue is visualized in all parametric images, and best seen in DV and Patlak Ki images. Patlak Ki showed a good correlation with 2TC Ki values (r = 0.858, p < 0.05) but less noise than 2TC images. A scanning time point of 30–35 min p.i. was then suggested for satisfactory tumor to background ratio. Conclusion Prostate cancer tissue is visible in most parametric images, and is better shown by Patlak Ki and 2TC DV images. Patlak Ki is consistent with, and thus is preferred over, 2TC Ki images for substantially quicker calculation. Based on the dynamic imaging analysis, a shorter uptake time (30–35 min) might be preferred for a better balance of tumor to background ratio.